Pemanfaatan Limbah Pangan Dalam Pembuatan Pupuk Organik Cair (POC) Di Desa Peresak, Batukliang - Billah, Septiana Nur Azizah; putri , erika aprilia; Faoziyah, Suhaebatul; septiana, nurazizahbillah; Saputra, Kurniawan Adi; kurnia, Rini; Gustina, Nila; Fawatissuwari, Anis; Gustavo, Alexandro; Hakim, Muhammad Qolbun; Randa, Mohammad Awi (Universitas Mataram, 2025)
Mataram University had a program called Community Service Program Empowerment of Village Communities in 2024/2025 implemented a work program for making Liquid Organic Fertilizer and socializing about procces of making Liquid Organic Fertilizer. This is based on the results of the analysis found on the waste processing system and the dominant amount of waste, namely food waste. The amount of food waste is more dominant because Peresak Village itself has quite a large agricultural and plantation area. Making this fertilizer uses simple materials such as food waste, barrels, yeast tape and so on. In making this fertilizer, it also takes time to ferment. The finished product then packaged in a container that has been given a sticker to make it neater and more attractive. Then, after the product is finished, outreach is carried out to the local community about how to make it, advantages, and so on.